Encouraging Students to Do Collaborative Learning In ESP Courses to Strengthen Students’ Oral Communication Skills - Agustina, Lia (JOLLT Journal of Languages and Language Teaching, 2022)
Collaborative learning is a strategy of teaching and learning by grouping students to work together to solve a problem, complete an assignment, and produce a product. It increases learners’ motivation and promotes a harmonious atmosphere, decreasing classroom anxiety and facilitating interaction discussion and an individual sense of self-centeredness. At the same time, it enlarges students' knowledge and skills. One of the important skills is oral communication. Oral communication is an important skill to learn as it could express ideas and opinions. It uses to discuss knowledge and bridge the communication for ones who do not understand English. Therefore, this study aims to encourage students to do collaborative learning to strengthen their oral communication skills. The researcher used the action research method to see the improvement of the students’ communication skills. The subject was 32 students of the Accounting Department State Polytechnic of Malang. The study resulted that most students showed an improvement in all four language skills, but speaking skills had the greatest improvement.